Dysteleology: A Classical Sunni Exegetical Perspective - Lala, Ismail (Theology and science, 2024)
This study conducts a qualitative analysis of teleological verses in the Qur’an, which reveals that they only demonstrate the power of God to resurrect, and the will of God to punish/ reward as He pleases, not His perfection. Subsequently, a quantitative analysis of the term most used to refer to teleological proofs (“āya,” sign) is conducted. It demonstrates that the term most frequently denotes miracles, emphasizing the power of God, and punishment, underscoring the will of God. The locational proximity of the putative teleological verses to eschatological ones corroborates that the overall objective of these verses is eschatological.